Demokracja i wolność sumienia oraz wyznania: [Democracy and freedom of consciences and religion] (Studia Prawnicze / The Legal Studies, 1981)
Democracy is a socio-political system in which the people or the nation are subjects of power, the system in which rights of man are recognized, respected and realized, in which equality at least as far as law is concerned is realized and in which the rule of law is respected. Speaking of rights of man we think of both fundamental and ordinary rights of man. Development of democracy requires the same, harmonious development and realization of political, personal, economic, social and cultural rights, both individual and collective. Among pOw litical and personal rights we should value the role of freedom of conscience and religion.It is regulated in Poland in the constitution and in several ordinary laws. As for its international sources we should mention International Pact of Political and Civil Rights of the OUN and also, partly, many other conventions and declarations of the OUN, UNESCO and regional ones. Up to now there is however no document of the OUN which would totally and exclusively regulate freedom of conscience and religion. Works on the draft of a declaration on elimination of intolerance and discrimination based upon religion or conviction are carried on since 1962. They are advanced already. In relation to now existing international regulation concerning freedom of conscience and religion this decla- ration will not add new elements. However, it will constitute a universal criterion to value realization of freedom of conscience and religion.It is the merit of S. Zawadzki that he appreciates the role of freedom in his research projects on development of democracy.